Heat transfer enhancement and free convection assessment in a double-tube latent heat storage unit equipped with optimally spaced circular fins: Evaluation of the melting process - Shojaeinasab Chatroudi, Ilia; Atashafrooz, Meysam; Mohammed, Hayder I.; Abed, Azher M.; Talebizadehsardari, Pouyan (Frontiers in Energy Research, 2023)
To overcome the weak conduction heat transfer of phase change materials (PCM), this investigation aimed to assess the behavior of a double-tube latent heat storage unit with circular fins through the charging process. The influence of free convection in the presence of fins of various arrangements and sizes was comprehensively studied. The geometrical characteristics of the fins, i.e., their size and number, were assessed to optimize their performance. Moreover, a sensitivity assessment was performed on the characteristics of the heat transfer fluid passing through the inner tube, i.e., the Reynolds number and temperature. Charging time diminished by 179% when nine 15 mm fins were added compared with the finless scenario, assuming the same phase change materials volume. Moreover, the system’s thermal recovery rate improved from 20.5 to 32.9 W when nine fins with the heigth of 15 mm were added. The use of more fins improved the thermal behavior of the phase change materials because of the higher total fin area. The melting time and heat storage rate changed by 76% and 71%, respectively, for the system with 19 fins compared with those with four fins. Moreover, the outcomes indicated that a higher heat storage rate can be achieved when the working medium’s faster flow and inlet temperature were used.